North Dakota lignite and Pittsburgh bituminous coal: a comparative analysis in application to CO 2 sequestration. (1st January 2011) - Haljasmaa, Igor V.; McLendon, T. Robert; Jikich, Sinisha A.; Goodman, Angela; Siriwardane, Hema; Soong, Yee; McIntyre, Dustin L.; Bromhal, Grant S.; Irdi, Gino A.; Dobroskok, Anastasia
Unmineable coal seams have been proposed as an option for carbon dioxide sequestration. Among key parameters necessary for assessing the suitability of a coal type (or specific coal seam) for sequestration are permeability and sorption capacity. Two ranks of coal (Pittsburgh seam bituminous and North Dakota lignite) are presented and compared in this paper. The lignite coal is technically preferable for sequestration. Permeability was affected by cracks/cleats, pressure variations and exposure time. Coal 'swelling' due to CO 2 sorption caused significant drops in permeability usually within several days which can significantly retard penetration rates of CO 2 into the sequestration target. Sorption times were determined at different confining and pore fluid pressures. Profiles of sorption gradients were determined. Sorption processes in coal cores may require days to approach equilibrium. Comparisons of coal cores were made with powdered coal studies (which have higher sorption, shorter times) for sorption isotherms.